Assessment of building behavior in slow-moving landslide-affected areas through DInSAR data and structural analysis. (15th November 2019) - Infante, Donato; Di Martire, Diego; Confuorto, Pierluigi; Tessitore, Serena; Tòmas, Roberto; Calcaterra, Domenico; Ramondini, Massimo
Highlights: A tool to detect spatio-temporal landslide-induced effects on buildings is presented. Building performace is investigated by DInSAR and structural analyses. Pre- and post-repair intervention is analyzed by DInSAR time-series. Abstract: Slow-moving landslides are a natural hazard which affects wide areas in the world and often are cause of significant damage to structures and infrastructures. Analysis of landslide evolution and of their interaction with existing man-made structures plays a key role in risk prevention and mitigation activities. To this purpose, a considerable interest towards innovative approaches has grown among the scientific community and land management institutions. In this work, Synthetic Aperture Radar data acquired by C-band and X-band sensors, combined with numerical analyses, have been successfully applied as a tool to detect spatial and temporal landslide-induced effects, in terms of deformations and structural behavior of a building affected by ground instability. Such approach has been applied to Moio della Civitella urban settlement (Salerno province, Italy), whose whole territory is interested by several slow-moving landslides. In detail, performance of a masonry building aggregate and the efficacy of restoration works have been investigated through an integrated assessment of displacement time-series pre- and post-repair intervention, and structural analysis performed with numerical code. Historical DInSAR data have permitted firstly the interpretation of building displacement time-series corresponding to pre- and post-works configurations; subsequently, the analysis of interpolated interferometric products has allowed to define gradient maps of vertical and horizontal displacements and to identify part of aggregate which can suffer a greater susceptibility to damage as a consequence of deformation gradients. Finally, the comparison of satellite and numerical data showed a substantial agreement with local failures and damage surveyed, thus confirming the capability of DInSAR technique to investigate building performance where no in situ displacement measurements were available.